Members of Casa de San Jose Inc. - Sahl, Ted (photographer):::Creator::::::::::::
Seated members of Casa de San Jose Inc. Recognizable members are seated on left hand side of table and are Dorene Tinney (fourth from left), Nevan (in the middle) and Lisa seated next to Nevan.